Development of fragility curves for C4-H buildings using consecutive modal pushover - Tirao, John Lemar M.
The development of fragility curves is important in the assessment of seismic demands of structures and disaster risk management. Fragility curves are used to determine the probability that a structure is exceeding a particular damage state under given ground motion intensities. Over the years, different nonlinear static procedures have been proposed and modified as an aid for seismic evaluation of buildings: majority of them failed to account for either higher-mode effects or rotation of plastic hinges or a combination of both. In the Philippines, the capacity spectrum method is used to estimate seismic demands of low-rise buildings, but it fails to give accurate results for high-rise structures. This paper utilizes consecutive modal pushover procedure, a methodology that is considered a breakthrough in tall building seismic evaluation, which employs single-stage and multi-stage pushover analyses to determine peak responses of high-rise structures. The method described in ATC 40 is used to generate fragility curves. The key building type under consideration is in the C4-H group, high-rise reinforced concrete moment-resisting frames with shear walls. Twenty-one C4-H buildings are modelled and analyzed in this paper, with varying structural configuration and shear wall dimensions.